Effect of vermicompost application on bioactive composition and antioxidant properties of Clinacanthus nutans Lindau / Zuhaili Yusof - Zuhaili , Yusof (2019)
Vermicompost is the product derived from composting of organic materials through the use of earthworms. The use of vermicompost as an alternative to chemical fertilizer is gaining attention, parallel to the rise in awareness on organic farming and sustainable agriculture. In this study, the effect of vermicompost application on the total phenolic content (TPC), total flavonoid content (TFC), total chlorophyll content (TCC), total anthocyanin content (TAC), total carotenoid content (TC) and antioxidant properties of Clinacanthus nutans Lindau were evaluated. The stability of all compounds after extract storage was also assessed. A field study employing a randomized complete block design (RCBD) with four treatment groups consisting of control plants (CC), plants supplied with chemical fertilizer (CF), plants supplied with vermicompost (VC) and plants supplied with both chemical fertilizer and vermicompost (MF) was conducted. Data analysis showed that CF plants contained the highest TPC (181.53 ± 35.58 mg GAE/g dry weight) and highest TCC (6090.97± 144.90 μg/g dry weight). On the other hand, CC plants showed the highest reading for TFC (276.25 ± 3.09 mg QE / g dry weight) and TC (520.47± 16.47 μg/g dry weight). Moreover, the antioxidant properties of the extracts were also assessed using DPPH, ABTS and FRAP assays. It was found that CC plants had the highest antioxidant potential against both DPPH and ABTS radicals and also the highest FRAP value. On the other hand, MF plants showed the lowest antioxidant potential. After 2 and 4 weeks of extract storage at -20oC and +4oC, TPC, TFC, TAC, TCC and antioxidant potential of the extracts were found to decrease but TC for all extracts increased significantly. Interestingly, extracts from VC and MF showed the lowest percentage of total phenolic, total flavonoid and total chlorophyll loss after 2 weeks of extract storage at -20oC and +4oC as compared to CC and CF. Besides that, extract from VC plants also exhibited the highest increase in TC after 2 and 4 weeks of extract storage at -20oC. At this juncture, it could be deduced that the application of vermicompost had little effect in the expression of phenolics, flavonoids, anthocyanin, chlorophyll and carotenoid in C. nutans Lindau plants. However, the extract from plants treated with vermicompost (both VC and MF) showed better stability as compared to CC and CF after being stored at different storage conditions. Pearson correlation analyses showed a significant correlation between TPC, TFC, TAC and TCC with FRAP, DPPH and ABTS.